Social engineering and the dangers of phishing - Gomes, V. (2021)
Social Engineering and phishing technique are subjects that have been evolving as the years pass, mainly through email, which is one of the most used communication tools in the world. Phishing emails are usually related to Social Engineering and may be proposed through links and / or attachments in this type of email, both of which are malicious propagation, and may be hacked into personal / confidential information or even complete control of the computer / email without the users noticing. Several studies have already been carried out showing that there have been more and more attacks of this type and increasingly impacting the population. The research described in this article aims to review prevention methods for this type of computer crime. The research included an exploratory study with a qualitative methodology, through interviews with professionals in the area of Computer Security and later a study with a quantitative methodology, through an online questionnaire.